ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN BUAH DI PASAR ARENGKA ( PASAR TRADISIONAL DAN GIANT HYPERMARKET (PASAR MODREN) DI KECAMATAN TAMPAN KOTA PEKANBARU - Eliza '; Ery Sayamar; Cory Kaswita (Fakultas Pertanian, Universitas Riau, 2011)
This research was conducted in Arengka Market and Giant Hypermart Pekanbaru. Theobjective of this research is to analyze the influence of cultural, personal, social andpsychological factors on consumer decision in purchasing fruits and to identify thedominant factors in influencing consumer to buy fruits in the markets. Research wascarried out for 6 months, from August until December 2010. Cultural factors weremeasured from buying habits, social factors were measured from the number of familymember and frequency of purchasing fruit in the markets. Personal factors weremeasured from the selection of the shops place and location, income and expenditure onfruits. The research results show that cultural factors do not influence the consumerpurchasing decision, while social, personal, and psychological factors affect consumerdecision in purchasing fruits. Among these factors, personal and psychological factorsare dominant factors influencing the consumer purchasing decision.Key words: fruit, traditional market, modern market